Židé a česká společnost v letech 1945-1948 - Šafirová, Lucie (Univerzita Karlova, Fakulta humanitních studií, 2011)
The following thesis outlines the situation of the Jewish minority in the czech society in 1945-1948. It follows the political situation and the social atmosphere in the postwar period and focuses on the specifics of the Jewish minority. By analyzing interviews with survivors of the Shoah describes how the period saw Jews themselves. It is especially focused on interpersonal relations that prevailed during the return of the survivors back to their homes. Chronologically describes the situation since the liberation of concentration camps, travel home, arriving back where it focuses on a reunion with loved ones, family support, relationships with friends, neighbors and acquaintances behavior and reactions of majority society. It describes how Jews coped with the return to normal life. Interpersonal relations in the postwar period depended mainly on the personality characteristics of people. But one can point out that the greatest support for returning were their relatives and friends who provide support to them in situations where they met with the negative attitude of Czech society. Keywords: post-war society, Jewish minority, interpersonal relations, Shoah witnesses Následující diplomová práce nastiňuje situaci židovské menšiny v české společnosti v letech 1945-1948. Sleduje politické poměry a společenskou atmosféru v poválečném období a zaměřuje se na specifika židovské minority. Pomocí analýzy rozhovorů s pamětníky šoa popisuje, jak dané období vnímali sami Židé. Soustředí se především na mezilidské vztahy, které panovaly během návratu přeživších zpět do jejich domovů. Chronologicky popisuje situace od osvobození koncentračních táborů, cesty domů, po příjezd, kde se zaměřuje na shledání s bližními, pomoc příbuzných, vztahy s přáteli, chování sousedů a známých a reakce většinové společnosti. Líčí, jakým způsobem se Židé vyrovnávali s návratem do normálního života. Mezilidské vztahy v poválečné době závisely především na osobnostních charakteristikách jednotlivých lidí. Lze ale poukázat na to, že největší ...